Managing environmental flows in Nepal’s rivers for a hydropowered future - KC, Jibesh; Nepal, Santosh; Shah, Ram Devi Tachamo; Eriyagama, Nishadi (CGIAR, 2024)
IWMI workshops introduced tools to measure environmental flows, and explored how to balance hydropower demands with the need to protect river health